Widespread low rates of Antarctic glacial isostatic adjustment revealed by GPS observations - Thomas, ID; King, MA; Bentley, MJ; Whitehouse, PL; Penna, NT; Williams, SDP; Riva, REM; Lavallee, DA; Clarke, PJ; King, EC; Hindmarsh, RCA; Koivula, H (Geophysical Research Letters, 2011)
Bedrock uplift in Antarctica is dominated by acombination of glacial isostatic adjustment (GIA) andelastic response to contemporary mass change. Here, wepresent spatially extensive GPS observations of Antarcticbedrock uplift, using 52% more stations than previousstudies, giving enhanced coverage, and with improvedprecision. We observe rapid elastic uplift in the northernAntarctic Peninsula. After considering elastic rebound, theGPS data suggests that modeled or empirical GIA upliftsignals are often over‐estimated, particularly themagnitudes of the signal maxima. Our observation that GIAuplift is misrepresented by modeling (weighted root‐mean-squaresof observation‐model differences: 4.95.0 mm/yr)suggests that, apart from a few regions where large icemass loss is occurring, the spatial pattern of secular icemass change derived from Gravity Recovery and ClimateExperiment (GRACE) data and GIA models may beunreliable, and that several recent secular Antarctic icemass loss estimates are systematically biased, mainly toohigh.